Is Timor-Leste's Growth Inclusive? - Craig Sugden (Asian Development Bank (ADB), 2012)
The newly independent Timor-Leste has established itself as one of the fastest growing economies in Asia and the Pacific. A concentration of economic activity in the capital has, however, raised the concern that the better off members of society are capturing most of the benefits. This study examines the first decade of the restoration of independence to assess if Timor-Leste's economic growth has been inclusive. Opportunity is found to have been provided to a larger share of the population, with those on lower as well as higher living standards enjoying more opportunity. Inequality in opportunity is generally in decline. It concludes that inclusive growth has been achieved. To maintain progress, it will be important to (i) prioritize support for the poorest Timorese, and (ii) achieve improvements in some lagging sectors, notably roads, water, and sanitation. Minimum standards of service delivery are proposed as a safeguard for the poorest Timorese.
hdl:11540/1268
Keywords: 330; Wirtschaftswachstum; Verteilungswirkung; Soziale Ungleichheit; Timor Leste